Flexible use of electricity in heat-only district heating plants - Trømborg, Erik; Havskjold, Monica; Bolkesjø, Torjus Folsland; Kirkerud, Jon Gustav; Tveten, Åsa Grytli (International Journal of Sustainable Energy Planning and Management, 2017)
European energy systems are in a period of significant transition, with the increasing shares of variable renewable energy (VRE) and less flexible fossil-based generation units as predominant factors. The supply-side changes are expected to cause large short-term electricity price volatility. More frequent periods of low electricity prices may mean that electric use in flexible heating systems will become more profitable, and such flexible heating systems may, in turn, improve the integration of increasing shares of VRE. The objective of this study is to analyze the likely future of Nordic electricity price levels and variations and how the expected prices might affect the use of electricity and thermal storage in heat-only district heating plants. We apply the North European energy market model Balmorel to provide scenarios for future hourly electricity prices in years with normal, high, and low inflow levels to the hydro power system. The simulation tool energyPRO is subsequently applied to quantify how these electricity price scenarios affect the hourly use of thermal storage and individual boilers in heat-only district heating plants located in Norway. The two studied example plants use wood chips or heat pump as base load representing common technologies for district heating in Norway. The Balmorel results show that annual differences in inflow is still a decisive factor for Norwegian and Nordic electricity prices in year 2030 and that short-term (daily) price variability is expected to increase. In the plant-level simulations, we find that tank storage, which is currently installed in only a few district heating plants in Norway, is a profitable flexibility option that will significantly reduce the use of fossil peak load in both biomass and heat-pump-based systems. Installation of an electric boiler in addition to tank storage is profitable in the heat pump system due to the limited capacity of the heat pump. Electricity will hence, to a large extent, replace gas when heat demand exceeds the capacity of the heat pump. For the bio-based plant, we find that an electric boiler in addition to tank storage is not profitable in the normal electricity price scenario. The electric boiler investments are only profitable when electricity prices are as low as in the high inflow scenario. In that case the electric boiler will provide 17% of the heat supply in the example plant. Fuel prices for peak load and electricity grid tariffs are found to be decisive factors for the electricity use – and therefore flexibility options – provided by heat-only district heating plants.